Frontal lobe and cingulate cortical metabolic dysfunction in acquired akinetic mutism: a PET study of the interval form of carbon monoxide poisoning - Tengvar, Christner; Johansson, Björn; Sorensen, Jens (Brain injury, 2004)
A middle-aged man suffering from acute carbon monoxide intoxication was clinically assessed to be in an akinetic and mute state. In order to elucidate regional cerebral disturbances, brain metabolism was investigated with fluoro-deoxyglucose positron emission tomography (18FDG-PET) 5.5 months after intoxication. Significantly reduced metabolic rates of glucose were revealed in selected brain regions, especially in both the frontal and anterior cingulate cortices, as well as in the subcortical white matter. Frontal and cingulate cortices showed a preserved metabolism of 35-53%, whereas the regional glucose consumption in cerebral white matter was reduced by more than 70%. In contrast, other areas of the brain such as the sensory-motor cortex, parts of the temporal lobes, basal ganglia and brainstem disclosed normal metabolic values. This lesion topography is discussed in relation to the development of akinetic mutism in the present case and in comparison with recent reports on the topic. Considering a plausible pathophysiology, akinetic mutism appears to be based on a different structural neuropathology when compared with the locked-in syndrome and the vegetative state. It is suggested that akinetic mutism is regarded as a specific condition characterized by injury of the frontal neuronal systems which promote executive functions.